Existence and Multiplicity of Nontrivial Solutions for a Class of Fourth-Order Elliptic Equations - Chun Li; Zeng-Qi Ou; Chun-Lei Tang (Abstract and Applied Analysis)
Using the Fountain theorem and a version of the Local Linking theorem, we obtain some existence and multiplicity results for a class of fourth-order elliptic equations.